Alveolar Bone Augmentation with Orthodontic Treatment Prior to Implant Placement: Part 1. Slow Orthodontic Extrusion - Vanduangden, Sinnapa; Thongudomporn, Udom (Thai Journal of Orthodontics, 2023)
For hopeless teeth, extraction and implant placement is usually indicated. Alveolar bone loss may lead to poor esthetic and compromise implant treatment success especially in periodontitis patients. Therefore, bone grafting may be necessary to promote alveolar bone thickness and height before implant placement. However, the treatment outcome of bone grafting is difficult to predict. Implant site development by slow orthodontic extrusion provides a non-aggressive alternative procedure to increase alveolar bone volume. Slow orthodontic extrusion is currently widely used in bone augmentation. Even so, there is no clear evidence for the effectiveness of this technique. Therefore, this review emphasizes on indication, contraindication, consideration of treatment planning, effectiveness, and complication of slow orthodontic extrusion for bone augmentation prior to implant placement.